Pengaruh Kompensasi Dan Disiplin Kerja Terhadap Kinerja Karyawan Pada PT Toarco Jaya Kabupaten Toraja Utara - Novita Raba’; Rati Pundissing; Randi Tangdialla (EKOMA : Jurnal Ekonomi, Manajemen, Akuntansi, 2024)
The aim of this research is to find out whether there is an influence of Compensation and Work Discipline on Employee Performance at PT Toarco Jaya, Toraja Regency. The data collection procedures for this research are: observation, questionnaires and interviews. The method used in this research is the Quantitative Method using the Multiple Linear Regression method and processed using SPSS 26. This research was conducted at the PT Toarco Jaya Office, North Toraja Regency. The technique that researchers used in sampling was the Saturated Sampling method, namely a sampling method using all members of the population, namely 34 samples. The results of calculations using the t test on the Compensation variable t count > t table with a value of (3.565) > (1.696) and on the Work Discipline variable t count > t table with a value of (18.220) > (1.696). The conclusion of this research is that Compensation and Work Discipline have a positive and significant effect on Employee Performance at PT Toarco Jaya, Toraja Regency.